Local Ownership in Asian Peacebuilding Development of Local Peacebuilding Models - Lee, SungYong (Cham, Switzerland Springer International Publishing Imprint: Palgrave Macmillan, 2019)
This book examines how local agencies in Cambodia and Mindanao (the Philippines) have developed their own models of peacebuilding under the strong influence and advocacy of external intervention. It identifies four distinct patterns in the development of local peacebuilders' ownership: ownership inheritance from external advocates, management of external reliance, friction-avoiding approaches, and utilisation of religious/traditional leadership. This book then analyses each pattern, focusing on its operational features, its significance and limitations as a local peacebuilding model. This study makes theoretical contributions to the academic debates on the 'local turn', local ownership, hybrid peace and everyday peace. Particularly, it engages in and further develops four specific lines of discussion: norm diffusions into local communities, patterns of local-external interaction, concepts of ownership, dual structure of power, and multiplicity in the identities of local. SungYong Lee is Senior Lecturer in Peace and Conflict Studies at the University of Otago, New Zealand, and is serving as a regional council member of the Royal Society of New Zealand. Dr Lee's current research mainly focuses on conflict resolution and post-conflict peacebuilding in civil war.
Chapter 1: Introduction -- Chapter 2: Peacebuilding and Local Peacebuilders in Cambodia and Mindanao -- Chapter 3: Ownership Inheritance from External Advocate -- Chapter 4: Management of External Reliance -- Chapter 5: Friction-avoiding Approaches -- Chapter 6: Utilisation of Religious/Traditional Leadership -- Chapter 7: Conclusion.
Keywords: Peace; Political leadership; Regionalism; Security, International